2018
DOI: 10.1590/s1980-6574201800020015
|View full text |Cite
|
Sign up to set email alerts
|

The acute hypotensive effect of resistance training performed with machines vs free weights in normotensive men

Abstract: To analyze if different resistance training (machine vs free weight) would have different acute hypotensive effect in active and normotensive individuals. Methods: Fifteen male volunteers (39.2±2.5 years) performed two different resistance exercise protocols, one on machinery and one with free weights for the similar muscle groups and volume (sets x repetitions). Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured at rest and during 60 minutes after the sessions. Results: There was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…There was a significant trend for the free-weight group for maximum strength compared to the machineload group, whereas there was no difference in the hypertrophy [23]. Free weight resistance training activates more muscle fibers and produces a greater hormonal response when compared to similar movements performed with a gym machine [24]. The percentage increase in pretest and post-test scores on strength, power, and muscle hypertrophy showed that the squat group using free weight was better than the gym machine group [25].…”
Section: Discussionmentioning
confidence: 78%
“…There was a significant trend for the free-weight group for maximum strength compared to the machineload group, whereas there was no difference in the hypertrophy [23]. Free weight resistance training activates more muscle fibers and produces a greater hormonal response when compared to similar movements performed with a gym machine [24]. The percentage increase in pretest and post-test scores on strength, power, and muscle hypertrophy showed that the squat group using free weight was better than the gym machine group [25].…”
Section: Discussionmentioning
confidence: 78%